Pengenalan Makanan Sehat Gizi Seimbang dengan Pendekatan Game Edukasi Pada Anak Usia Sekolah - Dhina Widayati; Linda Ishariani; Diana Rachmania (STIKES dan AKZI Karya Husada Kediri, 2022)
Children are the descendants of the nation and serve as the next generation of the nation. Therefore, it is important to protect the health of children. One effort you can make is to introduce healthy foods in a balanced diet. The current guidelines for healthy eating are based on the concept of balanced nutrition and are a revised version of the old Four Healthy His Five Complete Concepts. This new concept should be socialized to be better known in the community, including school requirements. This non-profit activity will promote school-aged children's understanding of nutritionally balanced and healthy eating by providing education on balanced and healthy nutrition using educational play media. is intended to deepen The activity was conducted in her three phases of planning, implementation, and evaluation, and was attended by 21 4th graders from SDN Palais 4. Before providing guidance, most students (43%) had proficiency in the subcategories, but after providing guidance, most students (58%) had proficiency. %) Had good knowledge of the category. The knowledge index of students in the good categories increased from just 19% to 58%. This Civil Service follow-up plan provides for regular monitoring and evaluation of child growth monitoring practices in collaboration with UKS schools. Strategies for delivering education through games can increase students' knowledge of healthy eating with a balanced diet. Educational game media can be one of the media that provides health education to all children.